Review of freshwater Bryozoa (Phylactolaemata) of Central Africa with descriptions of two new species - Wood, Timothy S. (Zootaxa, 2020)
The Royal Museum of Central Africa at Tervuren, Belgium, includes a small collection of freshwater bryozoans from Congo and Rwanda. Included are: Plumatella philippinensis with both statoblast types, as well as holotypes of Plumatella ruandensis Wiebach, 1964, Plumatella marlieri Wiebach, 1970, and Plumatella pseudostolonata Borg, 1940. There are also two new species which had been previously misidentified: specimens designated as Plumatella javanica are now recognized as P. wiebachi n. sp.; and specimens labeled Stolella indica now recognized as Plumatella kisalensis n. sp. This paper includes full descriptions of the new species as well as fresh descriptions and illustrations of other species in the collection.